CURRENT CHALLENGES FOR THE INTEGRATION PROCESSES IN THE SOUTHERN CAUCASUS: EUROPEAN AND EURASIAN DIMENSIONS - ALEXANIAN, Ashot (CENTRAL ASIA AND THE CAUCASUS, 2014)
The existing political, socioeconomic, and spiritual-cultural contradictions and conflicts in the Southern Caucasus can only be overcome by means of efficient European integration and Eurasian reintegration of the countries that belong to this region. The South Caucasian countries have been carrying out reforms in all spheres of social life within the framework of European integration. These reforms were aimed at ensuring sustainable development and chiliarches harmonization based on the European social model and, therefore, promoted internal and international integration. This has created prerequisites for establishing democratic institutions and rapidly forming a civil society; it has also raised government and local self-administration effectiveness, as well as the level of public capital, legal culture, and social security of the population. The obligations in the South Caucasian countries have taken upon themselves within the framework of international (including European) organizations has helped to overcome political instability, ethnic conflicts, social differentiation, and other destructive processes. The emergence of new dividing lines indicating the huge differences between the highly incompatible European and Eurasian integration projects threatens to destabilize the Southern Caucasus.It is also important to keep in mind that the Eurasian reintegration project, which embodies a modern development concept, is still coming to fruition. It has yet to undergo the social verification and instrumentalization so necessary in the current reality of the “knowledge society.”